Deciphering Degassing and Source Effects in Cl Isotopes in Melt Inclusions: The Possible Role of Amphibole in the Magma Source of Stromboli (Aeolian Island Arc) - Bouvier, Anne-Sophie; Rose-Koga, Estelle F.; Chapuis, Alexis (Frontiers in Earth Science, 2022)
Chlorine isotopes have emerged as a new geochemical tool over the past 15 years. Most of the data consist of bulk rock data, with a minority carried out in situ on melt inclusions using secondary ion mass spectrometry. More data are necessary to understand the relationship between 37Cl measured in melt inclusions and that in bulk rocks from the same volcanic center. Here we have analyzed a suite of melt inclusions entrapped in olivine Fo63-85, as well as some from clinopyroxene crystals, from a single hand-sample from the Vancori unit of Stromboli, Aeolian Islands. The 27 selected melt inclusions have major element compositions ranging from high potassium alkali basalt to evolved shoshonite. Their 37Cl vary from -2.6 ± 0.1‰ to +1.2 ± 0.2‰, a far larger range than for Stromboli bulk rocks. In this dataset, the 37Cl variation in melt inclusions is not related to Cl degassing, or to fractional crystallization. Instead, correlations between 37Cl and S/Cl, K2O and trace element ratios suggest mixing of two Cl endmembers with distinct 37Cl signatures. A first endmember is characterized by high potassium alkali basalt compositions, high Ba/La (~28), high S/Cl and high 37Cl (> 1‰), confirming the influence in the mantle source of an aqueous fluid and providing a new constraint on its composition: that it derives from the breakdown of amphibole. The second endmember has a more evolved composition, high La/Yb, low S/Cl and low 37Cl (<-2‰), identifying the influence of a solute-rich component derived from subducted sediments. The 37Cl data thus help refine the two sources initially identified from bulk rock studies and 37Cl proves to be a potential tracer for amphibole.